(untitled) (The Saraswati Review, 2024)
In the realm of literature, graphic novels have become much more prominent as a vibrant and versatile medium in recent years. This study explores the intricate fusion of narrative and visual elements within graphic novels, with an emphasis on how all of these elements work together for conveying complex stories and themes. As the medium continues to evolve, understanding the literary techniques employed becomes paramount for scholars, artists, and readers alike. The literature review traces the historical development of graphic novels, emphasizing their evolution from comic books to a legitimate literary form. Acknowledging seminal works and scholars in the field, this paper establishes a foundation for the exploration of narrative and visual techniques within the medium. Our methodology is rooted in content analysis and case studies, examining a diverse selection of graphic novels. These novels are chosen for their exemplary use of literary and visual techniques, reflecting a broad spectrum of themes and styles within the medium. In analyzing narrative techniques, we dissect the adaptation of traditional literary elements, including plot, character development, and dialogue.